(untitled) (Actualizaciones en Sida e Infectología, 2021)
When January 2020 began and we received news of a new virus, SARS-CoV-2, appearing in the Chinese province of Wuhan, thinking in terms of a pandemic was a long way off. The memory of the images in medical history books of the Spanish flu epidemic of 1918 was, up to that time, the most approximate idea of a pandemic. Although many of us had gone through the 2009 influenza pandemic, the situation was different: at that time we had antiviral treatment and, in addition, there was already a flu vaccine, to which the H1N1 variant only had to be added. But the case of COVID-19 was different, as we knew absolutely nothing about the new virus. Its great transmissibility meant that frontiers were erased, knowledge was transmitted rapidly, and health personnel took on a task without timetables or breaks. We reached 2021 with a lot of uncertainty, but always certain that the way forward was to have a transdisciplinary approach, that it was a problem that had to be tackled from multiple perspectives, and that having learned the added value of teamwork was crucial. The SADI Congress was not exempt from all the ups and downs mentioned above, and we had to adapt to the changes. But the challenge that this implied was reflected in an activity that allowed us to be close in a different way, reaching many people with a multidisciplinary approach. And in the midst of so much healthcare work, having been able to do research -which this year added a very valuable plus- showed that as long as our curiosity for information to be used for the benefit of our patients remains active in us, we will be on the right path in our profession. This pandemic has taught us a very strong lesson: we were able to recognize the value of working together and respecting the work of others -where we are all necessary in the chain, but we must also learn to treat nature well, not to contaminate water, to use resources rationally and to use and dispose of antimicrobials correctly, because the impact of not doing so is one very serious. This is a very important lesson, and if we are really going to learn it, from our place as a scientific society we will have to reinvest in education, research and sharing experience and knowledge, because this enriches us as people and as professionals. Then, I believe, we will have learned some lessons for the next pandemic.